An Estimation of Blood Glucose Level in Children with Early Childhood Caries- A Retrospective Study - Prabhav Kumar Iyer1 , Geo Mani2 , Sarvana Dinesh S.P3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
ECC is one of the most common oral conditions seen in children. It is primarily seen on the central incisorsin the form of a white spot, which later spreads to the posterior teeth as well. This is a serious concern forthe biological and the social life of a child. Treatment of this condition is also expensive making it difficultfor the economically backward to avail treatment. It has a lot of etiological factors including diet, socioeconomic status and poor oral hygiene. It is a condition seen in children below the age of 6. The aim of thisstudy is to find the level of blood glucose in children with early childhood caries and to evaluate whetherthere are any abnormalities in blood glucose level compared to normal reference level. A retrospectivedescriptive study was conducted using patient records of a university dental hospital in Chennai from June2019-March 2020 among patients diagnosed with ECC who had their blood sample taken and their bloodglucose levels recorded. Descriptive statistical tests were employed.Point biserial correlation analysis wasdone to find out the relationship between blood glucose levels in boys and girls with ECC. ECC was mostprevalent in the age group of 3 and the mean blood glucose of the participants was found to be 88.22 mg/dl.There was no significant correlation or difference in the mean blood glucose level of males and females withECC (Point biserial correlation coefficient=0.07). Based on the results, there were no abnormalities in bloodglucose values of children with ECC.